Prevalence of metabolic syndrome in individuals undergoing comprehensive cardiac and general medical check-up at Kathmandu Medical College Teaching Hospital - Karki, D B; Neopane, A; Joshi, S; Pant, Subash; Sharma, Lucky; Shrestha, Pradeep; Yogal, Rijendra (Journal of Kathmandu Medical College, 2014)
Background: Metabolic syndrome represents a constellation of metabolic derangements including insulin resistance, diabetes mellitus, obesity, dyslipidaemia and cardiovascular disease. Since it is associated with higher risk of coronary artery disease and diabetes mellitus, timely detection is important. Objectives: The main objective of the study was to find out the prevalence of metabolic syndrome in individuals undergoing comprehensive cardiac and general medical check-up at Kathmandu Medical College Teaching Hospital. The other objectives were to find the gender and ethnic prevalence of this condition. Methods: This is a hospital based cross-sectional study conducted at Kathmandu Medical College Teaching Hospital among 389 healthy participants of both gender and above 20 years of age who underwent comprehensive cardiac and general medical check-up. Metabolic Syndrome was diagnosed using US National Cholesterol Education Program Adult Treatment Panel III. Results: Out of the 389 subjects, 56 persons were found to be having metabolic syndrome (14.40%). Metabolic syndrome was more common in female and obese people and the prevalence did not differ with ethnicity. Conclusion: The prevalence of metabolic syndrome in the present study has been found to be 14.40 %. It is important to diagnose this condition in time so that subsequent complications can be prevented. Journal of Kathmandu Medical College Vol. 2, No. 3, Issue 5, Jul.-Sep., 2013 Page: 112-116 DOI: http://dx.doi.org/10.3126/jkmc.v2i3.9934 Uploaded date : 2/28/2014